Pengaruh Variasi Media Pendingin Proses Quenching Terhadap Mikrostruktur dan Sifat Mekanik Baja Hadfield - Ilham Azmy (Infotekmesin, 2022)
Manganese steel contains 1,2% C and 12% Mn generally recognized as Hadfield steel. Based on the high composition of C and Mn elements, the main structure of this steel is dominated by an austenite matrix that surrounded the carbide phase on the grain boundary. This structure is usually brittle which leads to improper high-loading conditions. To overcome this problem, the experimental method was carried out by heating Hadfield steel to a temperature of 1000 oC, then followed by a quenching process using cooling media variations namely water and salt bath (20 wt.% NaCl solution). These cooling media variations aim to determine the level of carbide formation which affects the microstructure and mechanical properties. From the test results, it was obtained that Hadfield steel with salt bath (20 wt.% NaCl) quenching variation has significant microstructure transformation which affects enhancement of the value of tensile and yield strength (809,5 and 542,4 MPa), hardness (238 HV), ductility and toughness.